An Assessment of U.S. Stream Compensatory Mitigation Policy: Necessary Changes to Protect Ecosystem Functions and Services1. (25th February 2013) - Bronner, Colleen E.; Bartlett, Amy M.; Whiteway, Sarah L.; Lambert, Douglas C.; Bennett, Sean J.; Rabideau, Alan J.
Abstract Compensatory mitigation of impacted streams and wetlands has increased over the past two decades, with the associated industry spending over US2.9 billion in aquatic restoration annually. Despite these expenditures, evaluations by the National Research Council and U.S. Government Accountability Office have provided evidence that compensatory mitigation practices are failing to protect aquatic resource functions and services, and vague federal policy and inadequate evaluation of compensatory mitigation projects are to blame. To address these weaknesses, an update to federal regulations on compensatory mitigation was released in 2008. Additionally, the 2012 Reissuance of Nationwide Permits, some of which affects compensatory stream mitigation, was recently published. Current policy, as reflected in these documents, still uses nonspecific language to direct compensatory stream mitigation leaving most implementation decisions to the local U.S. Army Corps of Engineers district. The majority of federal mitigation policy has focused on wetland compensation, with other aquatic resources receiving less attention (e.g., streams). In this article, weaknesses of current policy are discussed, as are suggested policy changes to minimize the loss of stream ecosystem functions and services. Compensatory mitigation policy should clearly define key terms, incorporate adaptive management procedures, and provide guidelines for determining mitigation costs and compensation ratio requirements.